Rolling across Europe's vanishing frontiers [electric railway technology]. - Kurz, H. (IEEE spectrum)
The European Union's market opening are leading on a broad front to the restructuring of the railway industry. State train monopolies are being dismantled and railway services are being transformed into private companies. For the new entities, the change means more than a reorientation to market imperatives-it means learning to step beyond their national frameworks and view themselves as service providers for all Europe. That, in turn, is affecting how electric locomotives are designed and built, especially for long-distance overnight and freight operations. In the long run, these policies will lead to higher performance and greater efficiency and will bring more traffic onto the rails. Because of open access to markets, too, European train manufacturers will enjoy larger batch orders, and rail service providers will enjoy lower costs per vehicle. The trend toward privatized rail service is in top gear by now. Britain is already far advanced. Germany negotiated the transformation in 1994 with great success. Now France and Switzerland are following in their tracks